Different garlic forms: (lobster, mashed, crushed) and their effect on quality qualities And the molecular life of the fermented cucumber and flavor (Journal of the College of Education for Women, 2019)
This study aimed to isolate and identifye the growth of microorganisms andtheir effect on pickled cucumber and cabbage, the study also investigated the effect ofgarlic (in the form of segments, chopped or crushed) on the mentioned pickled –foodfeatures . Furthermore, a sense based comparison is made between vinegar-preservedsamples and vinegar-garlic preserved ones.The following results have been obtained:1- The isolation of staph. aureus alone from the samples and the study of its physicaland biochemical features.2- The fresh garlic (segments, chopped and crushed) with concentration of 5%, 7.5%,and 10% showed a damaging percentage of 100% to bacterial growth of staph. Aureusafter 24 hours of incubation time compared to the control sample which a mounted to5.7x104 cell/ml.3- Decrease in pH values in pickled cucumber and cabbage samples as a result ofacid production by lactic–acid bacteria. The final values for the pickled cucumberwere 3.2 and for the pickled cabbage 3.4.4- The results also indicate that the pickled cucumber and cabbage with garlic atvarious concentrations in their three forms (segment, chopped and crushed) did notshow any signs of waste after storage, where as such signs appeared in pickledcucumber and cabbage not treated with garlic after two months of storage.Thisconfirms that garlic has an active and positive effect as a food – preserving materialon a ccount of the vital and anti – bacterial compounds contains.